Progressive pulmonary fibrosis in patients with connective tissue disease-associated interstitial lung disease: An explorative study - Jakob Höppner; Maximilian Wollsching-Strobel; Falk Schumacher; Wolfram Windisch; Melanie Berger (Archives of Rheumatology, 2024)
Objectives: The aim of this study was to identify differences and similarities between connective tissue disease (CTD) patients with and without progressive pulmonary fibrosis (PPF) by applying the new guidelines. Patients and methods: Patient characteristics and disease courses from medical records of 50 CTD-associated Interstitial lung disease (ILD) patients (33 females, 17 males; mean age: 60.1±12.9 years) were longitudinally studied between January 2018 and May 2022. Respiratory involvement in CTD patients was described, and differences in CTD patients who developed PPF compared to those who did not were identified by the 2022 ATS (American Thoracic Society)/ERS (European Respiratory Society)/JRS (Japanese Respiratory Society)/ALAT (Asociación Latinoamericana de Thórax) Guidelines on Idiopathic Pulmonary Fibrosis and Progressive Pulmonary Fibrosis in Adults. Results: In the majority (74%) of patients, CTD was diagnosed before ILD onset. Nonspecific interstitial pneumonia was the most common high resolution computer tomography pattern, followed by the usual interstitial pneumonia pattern. On pulmonary function test, 38% had a restrictive pattern at baseline. Patients without PPF tended to have worse lung function at baseline and increased macrophage count in bronchoalveolar lavage than patients with PPF. Conclusion: In patients without PPF, disease progression may be missed, resulting in inadequate management. Interdisciplinary management of patients with CTD with the participation of pulmonologists and precise lung function diagnostics is recommended.